CULTURAL-HISTORICAL AND LINGUOCULTURAL ASSOCIATIONS OF RHYMING SLANG (HISTORICAL PERSONALITIES AND EVENTS OF THE NEW PERIOD IN THE HISTORY OF ENGLAND) - Yu.V. Gorshunov (Многоязычие в образовательном пространстве, 2023)
Samples of rhyming slang expressions that refer to some important events of the new period of English history or are based on the names of historical and legendary figures of past epochs are considered in the article. They are cultural and historical onomastic items that are reflected in the collective memory of the British and are thus included into the so-called “relevant background knowledge” and “background knowledge of cultural heritage.” The article aims at describing the socio-historical associations of rhyming slang associated with the names of historical and legendary figures of past epochs and important events in the history of England. The topic is examined using samples of rhyming slang expressions selected from authoritative dictionaries of general and rhyming slang by using a continuous sampling method. The rhymes referring to some historical figures are cultural and historical items, containing precedent onyms and reflecting the tendency to create new onomastic rhymes based on the names of celebrities from the world of cinema, mass culture, pop music, sports, politics, etc. The socio-historical associations of rhyming slang have not yet been the subject of special analysis. Undoubtedly, they deserve linguistic and sociocultural description. The author draws attention to a special layer of vocabulary and phraseology, the analysis of which sets a new promising vector for the study of rhyming slang, containing cultural and historical items that have linguocultural value. Specialists in intercultural communication, linguoculturology, linguistic and regional studies, contrastive linguistics of the English and Russian languages, foreign (English) history, cultural speech and the practice of teaching English may find the results of the study useful and interesting.